changes in law because of cultural change | تغير الأحكام بتغير العرف - Siti Hanna (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2010)
TI1e topic of the research is about the change of law based on the change ofcustom. This research concludes that not all of custom can influence the changeof law. Basically, custom divided into two types: permanent and temporary.TI1e temporary custom caimot influence a law. Titis research describes views ofschool musliin scholars such as Hanafitic, Malikite, Shafiite, Hai1balite andcontemporary muslim scholars. This research refers to the classic and modembooks by reading-critical analysis.